The Role Of Human Resource Quality In Career Development - Nashrullah; Utami Yulihapsari, Ika (Yayasan Pendidikan Belajar Berdikari, 2024)
High-quality staff resources will result in a strong dedication to doing regular duties in accordance with their individual roles and functions in a more efficient, effective, and productive manner. As a result, efforts to increase the quality of human resources might focus on these two areas. Thus, human resource management plays an increasingly essential role in all personnel activities in order to build dependable human resources capable of contributing to the growth and advancement of government organizations. This study seeks to examine the impact of career advancement, work relationships, and work motivation on employee job satisfaction. The data was collected by distributing a questionnaire to around 225 respondents. The population and sample for this study were textile workers in Sumedang, and the analytic technique was SPSS software. This study discovered that career growth, work connections, and work motivation all had an impact on employee job satisfaction.